2021
DOI: 10.3892/ijmm.2021.4930
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and perspectives for immunotherapy in oesophageal cancer: A look to the future (Review)

Abstract: Oesophageal cancer is one of the most aggressive malignancies with limited treatment options, thus resulting in a high morbidity and mortality. With 5-year survival rates of only 5-10%, oesophageal cancer holds a dismal prognosis for patients. In order to improve overall survival, the early diagnosis and tools for patient stratification for personalized treatment are urgent needs. A minority of oesophageal cancers belong to the spectrum of Lynch syndrome-associated cancers and are characterized by microsatelli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 122 publications
(75 reference statements)
0
2
0
Order By: Relevance
“…In other words, a suitable biomarker can help us further screen out potential benefit groups for immunotherapy for EPC. Among the common immunotherapy biomarkers, the expression of PD-L1 has been most extensively studied (15). In a meta-analysis involving 4,174 patients with advanced tumors (including lung cancer, kidney cancer, head and neck cancer, melanoma, and urothelial cancer), the patients received nivolumab, pembrolizumab, or atezolizumab treatment, respectively, and the analysis results showed that both PD-L1-positive and PD-L1-negative patients can benefit from PD-1 or PD-L1 blocking therapy, in which the survival benefit of pembrolizumab treatment for PD-L1-negative patients was minimal.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, a suitable biomarker can help us further screen out potential benefit groups for immunotherapy for EPC. Among the common immunotherapy biomarkers, the expression of PD-L1 has been most extensively studied (15). In a meta-analysis involving 4,174 patients with advanced tumors (including lung cancer, kidney cancer, head and neck cancer, melanoma, and urothelial cancer), the patients received nivolumab, pembrolizumab, or atezolizumab treatment, respectively, and the analysis results showed that both PD-L1-positive and PD-L1-negative patients can benefit from PD-1 or PD-L1 blocking therapy, in which the survival benefit of pembrolizumab treatment for PD-L1-negative patients was minimal.…”
Section: Discussionmentioning
confidence: 99%
“…Biomarker research is underway, to select the potential patients most likely to benefit from therapy and spare others from side effects (e.g., inflammation of skin, intestines, endocrine system, and liver) and failure of treatment. [3]…”
Section: Introductionmentioning
confidence: 99%